Perlindungaan Hukum Terhadap Anak Korban Pemerkosaan Di Bawah Umur Perspektif Hak Asasi Manusia. - Ramadhani, Mahfud; Atharwan, Emilson (Institut Agama Hindu Negeri Tampung Penyang Palangka Raya, 2023)
Violence against children is a form of crime that is done intentionally. One form of crime against children is sexual crime in the form of rape. Rape is a form of crime committed against women by coercion, violence or threats of violence. Legally of course this action is strictly prohibited, moreover the victims are children. So that children who are victims of rape must be given legal protection. The legal protection that must be given to children who are victims of rape is to receive rehabilitation from the government both physically and mentally, spiritually and socially, besides that their privacy must be protected, their good name is protected and maintained, their safety as well as witnesses to victims is the responsibility of the government, and children who are so the victim has the right to always know the progress of the case he is facing. Then the status of children as victims and witnesses must also be protected by law. This is clearly a human right that is the victim of Susila's crimes, especially children.